Kegiatan “Bersama Orang Tua” Terhadap Kreativitas Belajar Siswa SDN Tenggilis Mejoyo I Surabaya - M. Amin (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
In the curriculum 2013 there are student activities with parents (formerly with homework/PR) is expected to develop and add activities according to the conditions and abilities of parents and students. Interaction between parents and students is very important to build a learning experience that can be at school an inseparable part of life at home. This study aims to find out how student activities with parents influence the learning creativity of first grade students at SDN Tenggilis Mejoyo I Surabaya. This type of research is quantitative, in collecting data using observation techniques and subjective tests with data analysis techniques using the percentage formula and Product Moment. The results found a positive relationship between activities with parents at home on student learning creativity with a pretty good correlation.